ANALISIS PEMAKAIAN SHUUJOSHI ZE DAN ZO DALAM KALIMAT BAHASA JEPANG - Isfaroh, Astnahati; Surono, Surono; Rosliana, Lina (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2015)
The purpose of this research is to identify the use of shuujoshi ze and zo inHakkenden comic so that the readers understand its use, especially in Japanesecomic. The data of the research is a Japanese comic by Miyuki Abe entitled